Mindfulness Matters: Untangling Entrapment and Mental Well-Being in Married Couples - Akyil, Yusuf; Erdinc, Beste; Satici, Seydi Ahmet (SPRINGER, 2025)
Individual experiences can influence the mental health of married couples. The objective of the present study is to investigate the mediating role of mindfulness in marriage between entrapment and mental well-being by examining the relationships between actors and partners. The actor-partner interdependence mediation model was employed to apply a dyadic approach to the data collected from 423 (N = 846) married couples for this purpose. The mean age of the women was 35.80 (SD = 9.57), while the mean age of the men was 39.0 (SD = 10.46). The results indicated that the relationships between entrapment, mindfulness, and mental well-being were substantial for both genders. It was discovered that the entrapment experienced by each of the couples predicted their own well-being through the mindfulness of the other in marriage in the context of partner effects. In other words, women's entrapment predicted their mental well-being, which in turn predicted men's mindfulness in marriage. Similarly, the mindfulness of women in marriage predicts the mental well-being of men. Consequently, it is anticipated that the well-being of both spouses will be enhanced if the mindfulness levels of individuals experiencing entrapment are high.
Keywords: Entrapment; Mindfulness; Mental well-being; Actor-partner interdependence model; Dyadic; MEDIATING ROLE; ANXIETY; DEFEAT; DEPRESSION; PARCEL; IMPACT; Psychiatry